(5u+4)(7+u)=0

Simple and best practice solution for (5u+4)(7+u)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (5u+4)(7+u)=0 equation:


Simplifying
(5u + 4)(7 + u) = 0

Reorder the terms:
(4 + 5u)(7 + u) = 0

Multiply (4 + 5u) * (7 + u)
(4(7 + u) + 5u * (7 + u)) = 0
((7 * 4 + u * 4) + 5u * (7 + u)) = 0
((28 + 4u) + 5u * (7 + u)) = 0
(28 + 4u + (7 * 5u + u * 5u)) = 0
(28 + 4u + (35u + 5u2)) = 0

Combine like terms: 4u + 35u = 39u
(28 + 39u + 5u2) = 0

Solving
28 + 39u + 5u2 = 0

Solving for variable 'u'.

Factor a trinomial.
(7 + u)(4 + 5u) = 0

Subproblem 1

Set the factor '(7 + u)' equal to zero and attempt to solve: Simplifying 7 + u = 0 Solving 7 + u = 0 Move all terms containing u to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + u = 0 + -7 Combine like terms: 7 + -7 = 0 0 + u = 0 + -7 u = 0 + -7 Combine like terms: 0 + -7 = -7 u = -7 Simplifying u = -7

Subproblem 2

Set the factor '(4 + 5u)' equal to zero and attempt to solve: Simplifying 4 + 5u = 0 Solving 4 + 5u = 0 Move all terms containing u to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 5u = 0 + -4 Combine like terms: 4 + -4 = 0 0 + 5u = 0 + -4 5u = 0 + -4 Combine like terms: 0 + -4 = -4 5u = -4 Divide each side by '5'. u = -0.8 Simplifying u = -0.8

Solution

u = {-7, -0.8}

See similar equations:

| 14x(-3x+5)=3 | | x*2+y=36 | | 14x(3x-5)=82 | | 9w^6+24w^5+16w^4=0 | | 3(3z+4)-4(2z-3)=8 | | 4y^4+18y^3-10y^2=0 | | 7z^2-20z-3=0 | | (3x)2-10= | | -18-12/-18+12= | | 8z-4(z-5)+4=4z-16 | | -15-(-4)-7= | | 8z-4(z-5)+4= | | (61000-x)/21350 | | 4x-3(3x-1)+12=15(x+9) | | -4(3-10)= | | -5+(-16)+9= | | 7n^2+14n+5=0 | | r=exp(0.09)-1 | | 20-11=3(x-3) | | 50+5y-17=17y-12-3y | | 36/-4= | | y=1x+16 | | 5h^3-30h^2+40h=0 | | 5(32)= | | -3/4p=18 | | 7-(3n-1)=4-4n | | 7/12-8/3x-5/83/8 | | 60=3x-3 | | +(-2)+5-(-2)= | | 3(3n-5)=(7n+5)+1 | | 5-3(t+3)=-1+2(t-3) | | 48=16(d+5) |

Equations solver categories